2017
DOI: 10.1093/sleep/zsx072
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Sleep Restriction on Neuronal Number and Volumetric Correlates of the Dorsal Respiratory Nuclei in a Rat Model

Abstract: CSR may potentially induce neuronal loss and structural changes in the dorsal respiratory nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In this study, the number of ganglionic cells in the CSD decreased in comparison to the control group, which is almost in line with the previous studies that showed a decrease in the number of neurons in different parts of the brain, such as the hippocampus, dentate gyrus [52], and dorsal respiratory nuclei in the brainstem following the CSD [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the number of ganglionic cells in the CSD decreased in comparison to the control group, which is almost in line with the previous studies that showed a decrease in the number of neurons in different parts of the brain, such as the hippocampus, dentate gyrus [52], and dorsal respiratory nuclei in the brainstem following the CSD [22].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the MMPM was designed to reduce individual stress, which included a recovery time window and provide social communication amongst animals without hindering free movement [22]. The tanks were filled with water to a level one cm below the surface of the platforms or the grid.…”
Section: Induction Of Chronic Sleep Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSR process continued for 21 days during which the laboratory animals were kept in the multiple-platform apparatus for 18 h (from 06:00 PM to 12:00 PM the next day), followed by a 6-h sleep recovery window (12:00 PM to 18:00). This time interval (06:00 pm to 12:00 pm the next day) was selected because, in this period, rats are known to attain the highest paradoxical (REM) sleep whereas the homeostatic pressure of non-REM sleep has been already yielded [21,22]. The environmental control group was positioned in the grid-floor box, in which animals were placed onto a stainless steel grid.…”
Section: Chronic Sleep Restrictionmentioning
confidence: 99%
“…The rods were fixed 2.3 cm apart letting the animals lie down while preventing them from falling in the water. The tails could have been immersed into the water [22,23].…”
Section: Chronic Sleep Restrictionmentioning
confidence: 99%